XAFKINTU. RECOVERING OUR ECONOMIC SYSTEM. BUILDING A NEW PROPOSAL - Anchio Boroa, Claura (Revista de Historia Social y de las Mentalidades, 2014)
This article aims to provide some thoughts on the use of Xafkintu, Mapuche form of economic exchange, establishing crossings with history and present days as an instance to think about this practice nowadays within a Mapuche economic development project. All this is seen from an intraethnic or emic perspective, and pointing to new challenges within the Mapuche movement.